2006
DOI: 10.1891/jcpiq-v20i4a002
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for Treatment of African American Couple Relationships

Abstract: As rates of separation and divorce among African Americans increase exponentially, development of effective treatment approaches for this population is particularly essential. Cognitive-behavioral treatment approaches targeting African American couple relationships by necessity must consider several risk factors specific to these couples, including experiences of racism and economic stress, as well as incorporate cultural resources and supports that may render these couples resilient to these stressors. In an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…The viewpoint that marriage was a gift from God probably aided in setting a firm base for the men's dedication to their wives (Lambert & Dollahite, 2008;Marks, 2005;Stanley & Markman, 1992). Indeed, previous work outlines the importance of spirituality and religion in intimate relationships among Blacks, in particular (Chatters, et al, 1999;Dainton, 1999;Hopkins-Williams, 2007;Hunt & Hunt, 2001;Hurt, 2013;LaTaillade, 2006;Pew Charitable Trust, 2009;Taylor, Chatters, & Levin, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The viewpoint that marriage was a gift from God probably aided in setting a firm base for the men's dedication to their wives (Lambert & Dollahite, 2008;Marks, 2005;Stanley & Markman, 1992). Indeed, previous work outlines the importance of spirituality and religion in intimate relationships among Blacks, in particular (Chatters, et al, 1999;Dainton, 1999;Hopkins-Williams, 2007;Hunt & Hunt, 2001;Hurt, 2013;LaTaillade, 2006;Pew Charitable Trust, 2009;Taylor, Chatters, & Levin, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Faith communities and religious doctrines may encourage marriage and positively influence an individual's choice to wed (Call, 1977;King & South, 2011;Otto, 1979). This is a particular consideration among Blacks given the high regard for spirituality and religion in Black culture (LaTaillade, 2006;Pew Charitable Trust, 2009;Taylor, Chatters, & Levin, 2004). Blacks are significantly more religious than the general population (Chatters, Taylor, & Lincoln, 1999;Pew Charitable Trust, 2009), and religious participation has been traced to Black marriage patterns (Hopkins-Williams, 2007;Hunt & Hunt, 2001;Hurt, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Within the empirical and theoretical literature, social ecological systems models (e.g., Bronfenbrenner, ) have emphasized the role of macrosystemic processes on relationship functioning, highlighting the impact of institutionalized racism and social justice inequalities (e.g., Boyd‐Franklin, ; Kelly, ; Szapocznik & Williams, ). More specifically, studies have shown that African Americans couples who experience more oppression and racism also report worse communication quality and increased relational aggression (e.g., Kelly & Floyd, ; LaTaillade, ). In addition to these representations of minority stress, racial ethnic minority individuals face lower employment rates as compared to majority identified individuals.…”
mentioning
confidence: 99%
“…Behavioral and cognitive-behavioral couple and family therapy has so far been limited in its adaptation to ethnic and racial minority populations, most likely because it is often employed with a "color-blind" approach that does not attend to cultural and societal influences upon individual and couples behavior (LaTaillade, 2006). For both couple and family behavioral and cognitive-behavioral approaches, additional research is needed to further explore the impact of race and ethnicity upon couple and family relationships and therapy, and diversity issues such as race and socioeconomic status should be addressed both in therapy and in future research (Kelly & Iwamasa, 2005).…”
Section: Diversity In Behavioral and Cognitive-behavioral Couple And mentioning
confidence: 99%
“…For example, enhanced cognitive-behavioral therapy (Epstein & Baucom, 2002) recognizes the environment's influence upon the couple, including family systems, community supports, stressors, and life circumstances. Similarly, IBCT ( Jacobson & Christensen, 1996) emphasizes a contextual focus and examines unifying themes underlying individuals' cognitions, behaviors, and emotional responses (LaTaillade, 2006). The utility of expanding these approaches to address multicultural and contextual factors is illustrated in the case example below.…”
Section: Diversity In Behavioral and Cognitive-behavioral Couple And mentioning
confidence: 99%